MX2-mediated innate immunity against HIV-1 is regulated by serine phosphorylation - Betancor, Gilberto; Jimenez-Guardeño, Jose Manuel; Lynham, Steven; Antrobus, Robin; Khan, Hataf; Sobala, Andrew; Dicks, Matthew DJ; Malim, Michael H. (Springer Nature, 2021)
The antiviral cytokine interferon activates expression of interferon-stimulated genes to establish an antiviral state. Myxovirus resistance 2 (MX2, also known as MxB) is an interferon-stimulated gene that inhibits the nuclear import of HIV-1 and interacts with the viral capsid and cellular nuclear transport machinery. Here, we identified the myosin light chain phosphatase (MLCP) subunits myosin phosphatase target subunit 1 (MYPT1) and protein phosphatase 1 catalytic subunit-β (PPP1CB) as positively-acting regulators of MX2, interacting with its amino-terminal domain. We demonstrated that serine phosphorylation of the N-terminal domain at positions 14, 17 and 18 suppresses MX2 antiviral function, prevents interactions with the HIV-1 capsid and nuclear transport factors, and is reversed by MLCP. Notably, serine phosphorylation of the N-terminal domain also impedes MX2-mediated inhibition of nuclear import of cellular karyophilic cargo. We also found that interferon treatment reduces levels of phosphorylation at these serine residues and outline a homeostatic regulatory mechanism in which repression of MX2 by phosphorylation, together with MLCP-mediated dephosphorylation, balances the deleterious effects of MX2 on normal cell function with innate immunity against HIV-1.
Keywords: Virología; Virus; Virology; HIV